2017
DOI: 10.1039/c7dt01549f
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium-catalysed hydroboration of aldehydes and aldimines

Abstract: The first examples for the rhenium-catalysed hydroboration of aldehydes, ketones and aldimines, including heteroaromatic quinoline, are reported herein. Reactions are remarkably chemoselective and tolerant of several functional groups. A wide array of rhenium complexes were efficient pre-catalysts for these hydroborations, including new low-valent complexes of the formula [Re(N-N)(CO)(L)]X (N-N = bipy derivative, L = labile ligand/solvent, and X = [BAr] and [B(3,5-di-tBu-cat)]), which have been characterized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…Compared to hydrogenation and hydrosilylation protocols, the hydroboration of carbonyl compounds is more efficient and can normally proceed at room temperature and with very low catalyst loading. [12][13][14][15] For instance, quite recently Gade et al reported that a manganese alkyl complex containing a chiral bis(oxazolinyl-methylidene)isoindoline pincer ligand has been used as a pre-catalyst for the enantioselective hydroboration of ketones under mild reaction conditions. 14 When compared to the transition metal catalyzed hydroboration of aldehydes and ketones which has been extensively investigated, the research on the catalytic hydroboration of carbonyl compounds using main group catalysts is less developed but has recently received considerable attention by many research groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to hydrogenation and hydrosilylation protocols, the hydroboration of carbonyl compounds is more efficient and can normally proceed at room temperature and with very low catalyst loading. [12][13][14][15] For instance, quite recently Gade et al reported that a manganese alkyl complex containing a chiral bis(oxazolinyl-methylidene)isoindoline pincer ligand has been used as a pre-catalyst for the enantioselective hydroboration of ketones under mild reaction conditions. 14 When compared to the transition metal catalyzed hydroboration of aldehydes and ketones which has been extensively investigated, the research on the catalytic hydroboration of carbonyl compounds using main group catalysts is less developed but has recently received considerable attention by many research groups.…”
Section: Introductionmentioning
confidence: 99%
“…14 When compared to the transition metal catalyzed hydroboration of aldehydes and ketones which has been extensively investigated, the research on the catalytic hydroboration of carbonyl compounds using main group catalysts is less developed but has recently received considerable attention by many research groups. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Compared to the precious and relatively toxic transition metals, amongst the main group metals, magnesium is earthabundant, non-toxic and inexpensive. The Mg-catalyzed hydroboration has been relatively well explored and has shown high reactivity in recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…B, 7 Al, 8 Ge, Sn 9 ) elements, as well as first-row (e.g. Ti, 10 Mn, 11 Fe, 12 Ni 13 ), group 6 (Mo 14 ) and late (Re, 15 Ru 16 ) transition metals recently reported. Despite the prevalence of Rh catalysts for the hydroboration of alkenes, 17 to the best of our knowledge, there has been only one stoichiometric example of the use of a Rh complex in the hydroboration of a carbonyl compound (benzaldehyde) reported in the literature to date.…”
mentioning
confidence: 93%
“…The hydroboration of C=O bonds is particularly impressive and it is strengthening its prestige as one of the utmost useful and most widely used reactions for the pharmaceutical industry . Carbonyl hydroboration catalysts include alkaline earth metals,, transition metals, group 13 metal catalysts, lanthanide, actinides, and other unique and sophisticated systems . In addition to the hydroboration of C=O bonds, the selective monohydroboration of carbodiimides to produce amidinates is also of great interest, since these systems play an important role in coordination chemistry …”
Section: Introductionmentioning
confidence: 99%